Analisis Minat UMK di Pasar Kuliner Alun-Alun Dadaha Tasikmalaya Terhadap Program Sertifikasi Halal Gratis Self Declare - Maulidia, Revina; Wildan, Asep; Guntari, Gita (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2023)
Based on Article 4 of Law Number 33 of 2014 concerning the Obligation of Halal Certification for MSMEs, MSMEs are one of the targets for Halal certification by the government. This is the government's effort to achieve Indonesia's goal of becoming the center of the world's halal industry and world fashion by 2024. Even though there are many small and medium businesses in Tasikmalaya, it seems that there has been no acceleration of halal certification for small and medium businesses. This is proven by the large number of still small and medium businesses that do not yet have halal certification, even though a free halal certification program has been implemented for the business actors themselves. This may be caused by a lack of information and understanding about halal certification among economic actors, especially in Tasikmalaya. The aim of this research is to find out how interested micro business actors in the Dadaha Square culinary market in Tasikmalaya City are towards the Free Halal Certification Program (SEHATI). This study used descriptive qualitative method. The aim of this research is to focus on Halal certification by collecting data through observation, interviews and recording techniques. The results of this research show that there is a lot of active interest in the free halal certification program carried out by small and medium businesses in the Alun Alun Dadah Tasikmalaya culinary market. Interest in the SEHATI program is influenced by internal factors such as 1) understanding of regulations, 2) knowledge of the SEHATI program, and 3) mindset of business world stakeholders. External factors are 1) government regulations, 2) Fulfillment of consumer rights and finally 3) Business development.